Chronic Non-cirrhotic Portal Vein Thrombosis with Cavernous Transformation Secondary to Protein C and S Deficiency - Majid, Zainab (Cureus, 2020)
Hereditary thrombophilia (HT), including the mutation of factor V gene and the deficiency of proteins C, protein S, or antithrombin, is a risk factor for portal vein thrombosis (PVT). PVT in acute cases is usually asymptomatic, whereas chronic cases mostly present as variceal bleeding and splenomegaly. However, cavernous transformation of the portal vein secondary to a long-standing PVT is very rare. Here we present a case of a 28-year-old female who was admitted with complaints of left upper abdominal pain and swelling for four to five years. Using laboratory and radiological examinations, a confirmatory diagnosis of cavernous transformation of a thrombosed portal vein due to protein C and S deficiency was made. The patient was managed through splenectomy with splenorenal shunting along with life-long prescription of anticoagulants.